2006
DOI: 10.1007/s10535-006-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct somatic embryogenesis and plant regeneration from leaf explants of Phalaenopsis amabilis

Abstract: Leaf explants of Phalaenopsis amabilis var. formosa formed clusters of somatic embryos directly from epidermal cells without an intervening callus within 20 -30 d when cultured on 1/2-strength modified Murashige and Skoog medium supplemented with 0.1, 1 and 3 mg dm -3 TDZ. Repetitive production of embryos involved secondary embryogenesis could be obtained by culturing segments of embryogenic masses on TDZ-containing media. Plantlet conversion from embryos was successfully achieved on regulator-free growth medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 17 publications
6
68
0
5
Order By: Relevance
“…White embryogenic calli was formed and covered almost all the surface of the leaf tip explants ( Figure 1A and 1B). Similar study was done by Chen & Chang (2006) with leaf tip explants of Phalaenopsis amabilis. Chen & Chang (2006) reported that when leaf explants of Phalaenopsis amabilis were cultured on hormone-free medium or medium added with NAA alone at 0.1 or 1.0 mg L -1 , the explants turned necrotic and no embryo was formed.…”
Section: Effect Of Pgrs On Embryogenic Callus Induction From Leaf Tipmentioning
confidence: 67%
See 1 more Smart Citation
“…White embryogenic calli was formed and covered almost all the surface of the leaf tip explants ( Figure 1A and 1B). Similar study was done by Chen & Chang (2006) with leaf tip explants of Phalaenopsis amabilis. Chen & Chang (2006) reported that when leaf explants of Phalaenopsis amabilis were cultured on hormone-free medium or medium added with NAA alone at 0.1 or 1.0 mg L -1 , the explants turned necrotic and no embryo was formed.…”
Section: Effect Of Pgrs On Embryogenic Callus Induction From Leaf Tipmentioning
confidence: 67%
“…Similar study was done by Chen & Chang (2006) with leaf tip explants of Phalaenopsis amabilis. Chen & Chang (2006) reported that when leaf explants of Phalaenopsis amabilis were cultured on hormone-free medium or medium added with NAA alone at 0.1 or 1.0 mg L -1 , the explants turned necrotic and no embryo was formed. However, in the presence of TDZ at 0.1, 1.0 and 3.0 mg L -1 either alone or in combination with NAA at 0.1 or 1.0 mg L -1 , somatic embryos (SE) directly formed at the surface of explants, without any interfering callus formation.…”
Section: Effect Of Pgrs On Embryogenic Callus Induction From Leaf Tipmentioning
confidence: 67%
“…Thus, protocols that provide clonal multiplication from different vegetative explants are necessary (Chugh et al 2009). Several explants have been used aiming at clonal propagation of orchids, such as root and stem meristems, inflorescence axis, flower bud and leaf apex (Colli and Kerbauy 1993, Chen and Chang 2006, Martin and Madassery 2006, Chugh et al 2009, Mulgund et al 2011. Although orchid micropropagation has shown great advances in the recent years, the widespread use of in vitro propagation is still limited by problems such as exudation of phenolic compounds from explants isolated from mature plants, somaclonal variation, and transplantation to the field (Chugh et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to regenerate Phalaenopsis orchids have been conducted by several researchers [2][3][4]. Propagation through PLBs has been obtained for the same orchid genus [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Propagation through PLBs has been obtained for the same orchid genus [4][5][6]. Different types of plant growth regulators (PGRs) and sources of explants have been used to induce PLBs.…”
Section: Introductionmentioning
confidence: 99%